Implementation of An Android-Based Mobile Application for Real-Time Student Learning Reports at SMP IDN Jonggol, West Java - Mulyana, Dadang Iskandar; Albahy, Abdurrahman A.; Khalid, Muhammad; Siregar, Muhammad Hafiz; Sadid, Muhammad Umar Arib (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This research implements an Android-based mobile application for real-time student learning reports at IDN Jonggol Middle School, West Java, which can provide information about real-time student learning reports at IDN Jonggol Middle School using an Android-based mobile application. This research was conducted because many parents of IDN Middle School students wanted to see their children's development directly. This research aims to implement an Android-based application to help parents of students at IDN Middle School monitor their children's learning progress in real time by applying technology that is currently developing and making it easier for parents to access information about their children's development anywhere and anytime. This qualitative research method aims to create a system and display the information presented in the application being created. To obtain data relating to student learning progress, we could access the data in spreadsheet form. With the Android application in this research, parents can access information about their child's learning progress directly anytime and anywhere.